O Estado e a educação religiosa: observações a partir da psicologia - Paiva, Geraldo José de (Estudos Avançados, 2018)
Religious education offered by the State is dealt with from the point of view of the adequate psychological conditions to be efficiently provided: interpersonal relations in a small group, distinctiveness of stimuli, and insertion into a broader reference group. As a philosophical basis, necessary to the psychological point of view, it presents Habermas’ and Ratzinger’s concept of democratic State, whose function is not only to tolerate but to promote cultural diversity of its component groups, according to the assumption of communicative action or dialog.